PARENTING ORANG TUA PETANI AGAR ANAK BERPERILAKU SESUAI SYARI’AT DI KUNCIA SUMATERA BARAT - sri hati putri (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2022)
Many guardians don't comprehend the example of nurturing great, so it makes freak conduct from their kids. For instance, the mentality of guardians who are excessively prohibitive of a kid's opportunity without really focusing on the kid to protect himself and communicate his thoughts. This study attempts to look at the perspectives on the books and the information introduced in this study is a subjective examination. The consequences of this study in view of the methodology of parental responsiveness and parental demandingness, it tends to be presumed that rancher guardians in Nagari Kuncia utilize tyrant nurturing. Dictator parent-youngster connections will generally be more agreeable, respectful and less forceful, yet they need self-assurance. The nurturing wills for the worker of Allah cherished in the Al-Quran Luqman Al-Hakim are valid monotheism, patient under Allah's watch, maintaining petitions and rebuking great and wickedness, persistence in confronting tests, denial of haughtiness, basic demeanor, don't rebuff kids truly, make an amicable family.